2017
DOI: 10.3906/sag-1507-102
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal findings and sequence analysis of target exons of calcium-sensingreceptor (CaSR) gene in patients with Sagliker syndrome

Abstract: Twenty-three patients and 23 control subjects were admitted to Balcalı Hospital of the Medical Faculty of Çukurova University in Turkey between 2009 and 2011. Chromosomal analysis was performed according to standard cytogenetic methods. Full sequencing of exons 2 and 3 of the CaSR gene was done. Results:We found base alterations and deletions in exons 2 and 3 of the CaSR gene. We also found a statistically significant increase in the rate of CAs in patients compared to controls. In total we evaluated 639 metap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Undergoing dialysis vintage, presenting high serum phosphate levels, and being female are risk factors for this disease[11,12]. Tunc et al[13] proposed that chromosome aberrations are associated with SS. Yildiz et al[14] reported genetic mutations in exons 1, 4, and 10 of the GNAS1 gene are related to SS and are also genetically predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Undergoing dialysis vintage, presenting high serum phosphate levels, and being female are risk factors for this disease[11,12]. Tunc et al[13] proposed that chromosome aberrations are associated with SS. Yildiz et al[14] reported genetic mutations in exons 1, 4, and 10 of the GNAS1 gene are related to SS and are also genetically predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of this syndrome include severe maxillary or mandibular deformities and benign oral tumors. The mechanism of craniofacial bone overgrowth is unclear but could be explained by intramembranous ossification activation in the craniomaxillofacial region [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is shown that missense mutations on the GNAS1 gene play an important role in SS pathogenesis. [2][3][4] The hallmark of SS is the presence of pronounced facial and skeletal alterations, with a preponderance of cases occurring in young women aged between 18 and 39 years. 5 These individuals exhibit severe manifestations, including maxillary or mandibular destruction, short stature, and fingertip deformities.…”
Section: Discussionmentioning
confidence: 99%